Fibroblast growth factor 23 and parathyroid hormone predict extent of aortic valve calcifications in patients with mild to moderate chronic kidney disease - Di Lullo, Luca (Clin Kidney J, 2015)
BACKGROUND: Cardiac valve calcifications are present in dialysis patients and regarded as dependent on a deranged mineral metabolism. Few data are available for patients with chronic kidney disease (CKD) not on dialysis. This study evaluates the potential association between the extent of cardiac valve calcification and levels of intact parathyroid hormone (i-PTH), phosphorus, calcium, 25-OH vitamin D, fibroblast growth factor 23 (FGF-23), Klotho and C-reactive protein (CRP) simultaneously measured in patients with mild to moderate CKD. METHODS: Consecutive non-hospitalized patients referring to five nephrology units were evaluated. Inclusion criteria were age >18 years, CKD Stages 3–4, and the presence of aortic and/or mitral valve calcification assessed by echocardiography as routinely clinical evaluation. Patients underwent clinical examination and routine biochemistry. Baseline i-PTH, phosphorus, calcium, 25-OH vitamin D, FGF-23, Klotho and CRP were simultaneously ascertained. RESULTS: Extent of aortic valve calcification (n = 100 patients) was moderate in 68 patients and mild in the remaining patients. Mitral valve calcification (n = 96 patients) score was 1, 2 and 3 in 61, 34 and 1 patients, respectively. In univariate analysis, no association was found between extent of mitral valve calcification and markers of mineral metabolism and CRP; aortic valve extent of calcification was positively associated with i-PTH (r(2) = 0.212; P = 0.03) and FGF-23 (r(2) = 0.272; P = 0.01), and negatively with Klotho (r(2) = −0.208; P = 0.04). In multivariable analysis, extent of aortic valve calcification was associated with FGF-23 (P = 0.01) and PTH (P = 0.01) levels. CONCLUSIONS: Extent of aortic valve calcification is associated to FGF-23 and PTH in naïve CKD patients with mild to moderate CKD. Further studies should examine whether FGF-23 assay should be included in routine clinical evaluation of CKD as part of cardiovascular risk stratification.